Impact of climate change on freshwater macronutrients and agricultural yields across Britain - Nathan Missault; Victoria A. Bell; David M. Cooper; Ryan T. Sharp; Andrew P. Whitmore; Alice E. Milne; Helen N. Davies (Journal of Environmental Management, 2026)

Rethinking land-use Strategies: A multi-objective analysis of combined sparing and sharing approaches applied across great britain - Imane El Fartassi; Ryan T. Sharp; Victoria A. Bell; Andrew P. Whitmore; Helen Metcalfe; Nathan Missault; John Redhead; David M. Cooper; Jonathan Storkey; Helen Davies; Theo Jackson; Kevin Coleman; et al. (Journal of Environmental Management, 2026)

Bioeconomy in countries of the Mekong region: Stakeholder understanding and perceptions in Thailand, Vietnam, and Laos - Radek Rinn; Martin Jankovský; Petra Palátová; Sandra Paola García-Jácome; Alice Sharp; Prasit Wangpakapattanawong; Nataša Lovrić; Manh Vu Van; Minh Doan Thi Nhat; Bounheuang Ninchaleune; Inta Chanthavong; Kongchan Doungmala (Forest Policy and Economics, 2024)

Implications and impacts of aligning regional agriculture with a healthy diet - Ryan T. Sharp; Angelina Sanderson Bellamy; Adrian Clear; Samantha Mitchell Finnigan; Ella Furness; Elliot Meador; Helen Metcalfe; Susanna Mills; Kevin Coleman; Andrew P. Whitmore; Alice E. Milne (Journal of Cleaner Production, 2024)

Dynamics of bacterial blight disease in resistant and susceptible rice varieties - Jennifer T. Niones; Ryan T. Sharp; Dindo King M. Donayre; Eula Gems M. Oreiro; Alice E. Milne; Ricardo Oliva (European Journal of Plant Pathology, 2022)
Bacterial blight ( X. oryzae pv. oryzae ) is a serious disease in rice across the world. To better control the disease, it is important to understand its epidemiology and how key aspects of this (e.g. infection efficiency, and spatial spread) change according to environment (e.g. local site conditions and season), management, and in particular, variety resistance. To explore this, we analysed data on the disease progress on resistant and susceptible varieties of rice grown at four sites in the Philippines across five seasons using a combination of mechanistic modelling and statistical analysis. Disease incidence was generally lower in the resistant variety. However, we found no evidence that the primary infection efficiency was lower in resistant varieties, suggesting that differences were largely due to reduced secondary spread. Despite secondary spread being attributed to splash dispersal which is exacerbated by wind and rain, the wetter sites of Pila and Victoria in south Luzon tended to have lower infection rates than the drier sites in central Luzon. Likewise, we found spread in the dry season can be substantial and should therefore not be ignored. In fact, we found site to be a greater determinant of the number of infection attempts suggesting that other environmental and management factors had greater effect on the disease than climate. Primary infection was characterised by spatially-random observations of disease incidence. As the season progressed, we observed an emerging short-range (1.6 m–4 m) spatial structure suggesting secondary spread was predominantly short-range, particularly where the resistant variety was grown.

Plant–pollinator interactions in a Mexican Acacia community - Nigel E. Raine; Alice Sharp Pierson; Graham N. Stone (Arthropod-Plant Interactions, 2007)

Rehabilitation of degraded forests in Thailand: policy and practice - Alice Sharp; Nobukazu Nakagoshi (Landscape and Ecological Engineering, 2006)